Food Neophobia Scale (FNS): Testing The Validity and Reliability of the Turkish Version in School-Age Children: Turkish Validity and Reliability Study - Elmas, Cemre; Kabaran, Seray (Progress in Nutrition, 2021)
Introduction: The aim of this study was to test the validity and reliability of the Turkish version of the Food Neophobia Scale (FNS). Materials and Methods: The study was conducted with school age children aged between 9-11 years (n=781) who were studying in primary schools in Turkish Republic of Northern Cyprus (TRNC) in the 2018-2019 academic year. The language validity, content validity, construct validity and reliability analyses of the scale were implemented. The standard Brislin procedure was applied for language validity studies. Exploratory Factor Analysis (EFA) was used to evaluate the construct validity of the scale. Cronbach alpha value was calculated in order to evaluate the reliability of the scale and test-retest method was applied since there was no other comparable scale. Results: In this study, Eigenvalue was found to be 4.873. This value shows that the scale has one factor in this study. In the one factor analysis, Kaiser-Meyer-Olkin (KMO) value was found to be 0.907. Bartlett’s test value was found to be significant ( (36)=3309.10, p